High mortality following revision hip arthroplasty for periprosthetic femoral fracture: a cohort study using National Joint Registry data. (5th December 2020) - Khan, Tanvir; Middleton, Rob; Alvand, Abtin; Manktelow, Andrew R. J.; Scammell, Brigitte E.; Ollivere, Benjamin J.
Abstract : Aims: To determine mortality risk after first revision total hip arthroplasty (THA) for periprosthetic femoral fracture (PFF), and to compare this to mortality risk after primary and first revision THA for other common indications. Methods: The study cohort consisted of THAs recorded in the National Joint Registry between 2003 and 2015, linked to national mortality data. First revision THAs for PFF, infection, dislocation, and aseptic loosening were identified. We used a flexible parametric model to estimate the cumulative incidence function of death at 90 days, one year, and five years following first revision THA and primary THA, in the presence of further revision as a competing risk. Analysis covariates were age, sex, and American Society of Anesthesiologists (ASA) grade. Results: A total of 675, 078 primary and 74, 223 first revision THAs were included (of which 6, 131 were performed for PFF). Following revision for PFF, mortality ranged from 9% at 90 days, 21% at one year, and 60% at five years in the highest risk group (males, ≥ 75 years, ASA ≥ 3) to 0.6%, 1.4%, and 5.5%, respectively, for the lowest risk group (females, < 75 years, ASA ≤ 2). Mortality was greater in all groups following first revision THA for PFF than for primary THA. Compared to mortality risk after first revision THA for infection, dislocation, or aseptic loosening, revision for PFF was associated with higher five-year mortality in all groups except males < 75 years with an ASA ≤ 2. Conclusion: Mortality risk after revision THA for PFF is high, reaching 60% at five years in the highest risk patient group. In comparison to other common indications for revision, PFF demonstrated the highest overall risk of mortality at five years. These estimates can be used in the surgical decision-making process and when counselling patients and carers regarding surgical risk. Cite this article: Bone Joint J 2020;102-B(12):1670–1674.